Ordering policies for a dual sourcing supply chain with disruption risks - Jingjing Zhu; Shaochuan Fu (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The main purpose of this article is to explore the trade-off between ordering policies and disruption risks in a dual-sourcing network under specific (or not) service level constraints, assuming that both supply channels are susceptible to disruption risks. Design/methodology/approach: Stochastic newsvendor models are presented under both the unconstrained and fill rate constraint cases. The models can be applicable for different types of disruptions related among others to the supply of raw materials, the production process, and the distribution system, as well as security breaches and natural disasters. Findings: Through the model, we obtain some important managerial insights and evaluate the value of contingency strategies in managing uncertain supply chains. Originality/value: This paper attempts to combine explicitly disruption management with risk aversion issues for a two-stage supply chain with two unreliable suppliers.
Keywords: 650; ordering policies; disruption risks; two-stage supply chain; dual sourcing; risk aversion; stochastic model